Empowering Language Learners: Unleashing the Potential of The Feynman Technique in English Language Acquisition - Bsharat, Tahani R. K.; Febrianingrum, Lasmi; Habibullah, Mosleh (Institut Agama Islam Negeri Madura, 2024)
Abstract: This study investigates the effectiveness of the Feynman Technique in enhancing English language learning (ELL) outcomes. As a relatively new approach compared to traditional language instruction methods, the Feynman Technique emphasizes deeper understanding, active learning, and metacognitive reflection. Using a mixed-methods quasi-experimental design with pre- and post-intervention assessments, alongside observations and interviews, this research explores its impact on language proficiency and learning experiences in L2 English learners. Results demonstrate a significant improvement in language proficiency, with scores increasing from an average of 65% in pre-intervention assessments to 82% post-intervention, indicating a 17% improvement. Additionally, students reported increased confidence and engagement. In conclusion, the Feynman Technique has the potential to revolutionize language education by enabling students to become more autonomous and capable in a global context.